Banderyzm. Przyczyny zbrodni ludobójstwa SB-OUN i UPA w czasie II wojny światowej - Partacz, Czesław (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The article presents the development of the Ukrainian integral nationalism directed at creating an authoritarian, National-Socialist government on the territories considered by the OUN activists ethnically Ukrainian lands. It was supposed to be an empire ruling over the Eastern Europe, encompassing the area of 1,200,000 square kilometers. The state was supposed to be ethnically uniform, without national minorities. Friendly minorities were supposed to be resettled, whereas the hostile ones — like Poles, Russians or Jews — were to be exterminated. This government was supposed to come into existence through the Nationalist revolution. In September 1939 and during the summer of 1941 these plans were not realized. In February 1943 OUN made a decision to start the revolution, the first phase of which was supposed to lead to the mass murder of the Polish population of the Volynian Voivodeship and Eastern Małopolska. OUN and its armed criminal squads, SB and UPA, murdered around 134,000–200,000 Poles inhabiting those lands. These murders caused flight and resettlement of the further several hundred thousand of Poles. The culture of the Eastern Marches of Poland was destroyed; four voivodeships were devastated. Ukraine did not gain independence. Joseph Stalin’s Soviet Union was the sole beneficiary of these events.
Keywords: banderyzm; ludobójstwo; ukraiński nacjonalizm; SB-OUN; UPA; II wojna światowa